Surface tension profiles of ethylene glycol under microwave radiation - Asada, M.; Kanazawa, Y.; Asakuma, Y.; Phan, Chi (Aabo Akademi University, 2014)
Surface tension of fluid is crucial for multiphase systems and is often manipulated during industrial processes by introducing surfactants. In this study, effect of microwave radiation on surface tension of ethylene glycol was investigated for new physical method to manipulate the surface tension without using chemicals. It has found that surface tension profiles of ethylene glycol during microwave are different with water. Moreover, convections in the water and ethylene glycol droplet during and after microwave radiation were compared to provide new understanding on the non-thermal effect of microwave.